The novel artemisinin imer Isoniazide ELI-XXIII-98-2 induces c-MYC inhibition, DNA damage, and autophagy in leukemia cells - Elbadawi, Mohamed; Boulos, Joelle C.; Dawood, Mona; Zhou, Min; Gul, Waseem; ElSohly, Mahmoud A.; Klauck, Sabine; Efferth, Thomas (Pharmaceutics, 2023)
The proto-oncogenic transcription factor c-MYC plays a pivotal role in the development of tumorigenesis, cellular proliferation, and the control of cell death. Its expression is frequently altered in many cancer types, including hematological malignancies such as leukemia. The dimer isoniazide ELI-XXIII-98-2 is a derivative of the natural product artemisinin, with two artemisinin molecules and an isoniazide moiety as a linker in between them. In this study, we aimed to study the anticancer activity and the molecular mechanisms of this dimer molecule in drug-sensitive CCRF-CEM leukemia cells and their corresponding multidrug-resistant CEM/ADR5000 sub-line. The growth inhibitory activity was studied using the resazurin assay. To reveal the molecular mechanisms underlying the growth inhibitory activity, we performed in silico molecular docking, followed by several in vitro approaches such as the MYC reporter assay, microscale thermophoresis, microarray analyses, immunoblotting, qPCR, and comet assay. The artemisinin dimer isoniazide showed a potent growth inhibitory activity in CCRF-CEM but a 12-fold cross-resistance in multidrug-resistant CEM/ADR5000 cells. The molecular docking of artemisinin dimer isoniazide with c-MYC revealed a good binding (lowest binding energy of −9.84 ± 0.3 kcal/mol) and a predicted inhibition constant (pKi) of 66.46 ± 29.5 nM, which was confirmed by microscale thermophoresis and MYC reporter cell assays. Furthermore, c-MYC expression was downregulated by this compound in microarray hybridization and Western blotting analyses. Finally, the artemisinin dimer isoniazide modulated the expression of autophagy markers (LC3B and p62) and the DNA damage marker pH2AX, indicating the stimulation of both autophagy and DNA damage, respectively. Additionally, DNA double-strand breaks were observed in the alkaline comet assay. DNA damage, apoptosis, and autophagy induction could be attributed to the inhibition of c-MYC by ELI-XXIII-98-2.
Dieser Artikel gehört zum Special issue "Natural products for anticancer application"
Gesehen am 01.08.2023